An effective approach for managing power consumption in cloud computing infrastructure - Abd S.K.; Al-Haddad S.A.R.; Hashim F.; Abdullah A.B.H.J.; Yussof S. (Elsevier B.V., 2023)
Bioinformatics; Carbon; Cloud computing; DNA; Energy utilization; Power management; Cloud computing infrastructures; Cloud computing services; DFGA; Lower-power consumption; Power aware architecture; Reduced power consumption; Resource utilizations; Vm migrations; Electric power utilization